Theoretical Study of the Electronic Properties of The Curcumin Molecule: Using Density Functional Theory (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This search aims to study electronic properties of the curcumin moleculewhich exist in two isomers, ketone and enol forms, and the effect of usingdifferent basis setsby relying on density functions theory (DFT) at B3LYP level.The hydrogen atom transfer from the central methylene (CH2) group to an oxygen atom to form strong intra-molecular hydrogen (O H) bond causes geometrical changes in two isomers; where the enol form is structure approximately planar but not completely planar for the ketone form.The results showed that the 6-311G+(d,p) basis set gave sat- isfactory results for calculations. As well as the findings of each of the total energy, the energy of the high occupied molecular orbital and energy gap confirm that the isomer ketone is more stable than isomer enol. Also the ketone has a high electron-accepting, as was proven by the values of the energy of lower unoccupied molecular orbital,ionization potential, electron affinity and electronegativity.